Sinergi Direktorat Preservasi dan Akuisisi ANRI dalam Menghadirkan Kembali Jejak Masa Lampau - Ananta Dharma Kusuma; Alfath Chordasyabana Sumar Danni; Annisa Amalia; Fandy Rizky Ramadhan; Syahrul Kurniawan (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Archives are one of the primary sources in historical writing. One of the government agencies engaged in archiving is ANRI or the National Archives of the Republic of Indonesia which is an archival institution at the central level. Various types of archives from the VOC era to the contemporary are stored neatly and well maintained so that the public can access them at any time through the services provided by ANRI for various purposes. The focus presented in this paper is on ANRI, especially the Directorate of Acquisition and Preservation. The formulation of the problems discussed, the first is an overview of the history of ANRI, the second is regarding the legal basis related to the ANRI acquisition and preservation work unit, and the last discusses the synergy between acquisition and preservation units in the archiving workflow at ANRI. The method used in this paper is a qualitative method with data collection in the form of literature reviews, interviews, and also observations. This paper was created with the aim of informing readers about ANRI's profile and explaining the description, functions and duties of the Directorate of Acquisition and Preservation.